Adubação orgânica e densidades de plantas em crotalária juncea antecedendo arroz - Sousa, Giulliana Mairana Morais de (Universidade Federal Rural do Semi-Árido, 2011)
Green manuring is the practice of incorporating undecomposed plant tissue to the soil, to maintain or increase soil fertility. One of the most used plants as green manure is Crotalaria juncea, with presents advantages compared to other legumes. This work was conducted with the objective of evaluating the effect of organic manures and plant densities on Crotalaria juncea growth, accumulation of nutrients in its shoots and in the soil, and also on rice yield. The trial was developed in an experimental area of Semiarid Federal Rural University, in Mossoró, RN, Brazil. Experimental design was a randomized blocks in a 4 x 3 factorial scheme, with four replications. Factors studied were organic manures (chicken manure, earthworm humus and control) and plant spacing (10 x 10, 14 x 14, 17x 17 and 20 x 20 cm). Determinations realized were: fresh and dry mass of shoot and root of crotalaria, shoot contents of N, P and K and soil pH, electrical conductivity (EC), PST and contents of C, N, P, K, Na, Ca and Mg after decomposition of crotalaria plants, and also rice production components (panicle number in 10 plants, grain weight in 10 plants; empty grain weight in 10 plants; mass of 100 grains). Data were submitted to variance analysis. The results related to the spacing were subjected to linear regression and data on the type of fertilization were subjected to Duncan test at 5% probability. Plant density of crotalaria provided a positive linear effect on shoot dry and green mass and per hectare accumulated amounts of N, P and K of shoot, and also a negative linear effect on root dry mass. Nutrient content per plant were not influenced by plant density and manure type, while manure type influenced only the P content per plant. Chicken manure provided the higher values of shoot fresh (24,55 t ha-1), and dry mass (5,89 t ha-1) and root dry mass (20,23 g) of crotalaria and the higher values of accumulated amounts per hectare of N(122,68 kg ha-1), P (33,38 kg ha-1) and K (78,00 kg ha-1) on shoot. Plant density of crotalaria did not influenced rice production components, while manure type only influenced mass of empty grains.
Organic manures and plant densities in crotalaria juncea preceding rice
Keywords: green manure; Crotalaria juncea L.; soil management; legumes; adubação verde; Crotalaria juncea L.; leguminosas; manejo do solo; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO